Eddy‐driven nutrient transport and associated upper‐ocean primary production along the Kuroshio. Issue 6 (22nd June 2017) - Uchiyama, Yusuke; Suzue, Yota; Yamazaki, Hidekatsu
Abstract: The Kuroshio is one of the most energetic western boundary currents accompanied by vigorous eddy activity both on mesoscale and submesoscale, which affects biogeochemical processes in the upper ocean. We examine the primary production around the Kuroshio off Japan using a climatological ocean modeling based on the Regional Oceanic Modeling System (ROMS) coupled with a nitrogen‐based nutrient, phytoplankton and zooplankton, and detritus (NPZD) biogeochemical model in a submesoscale eddy‐permitting configuration. The model indicates significant differences of the biogeochemical responses to eddy activities in the Kuroshio Region (KR) and Kuroshio Extension Region (KE). In the KR, persisting cyclonic eddies developed between the Kuroshio and coastline are responsible for upwelling‐induced eutrophication. However, the eddy‐induced vertical nutrient flux counteracts and promotes pronounced southward and downward diapycnal nutrient transport from the mixed‐layer down beneath the main body of the Kuroshio, which suppresses the near‐surface productivity. In contrast, the KE has a 23.5% higher productivity than the KR, even at comparable eddy intensity. Upward nutrient transport prevails near the surface due to predominant cyclonic eddies, particularly to the north of the KE, where the downward transport barely occurs, except at depths deeper than 400 m and to a much smaller degree than in the KR. The eddy energy conversion analysis reveals that the combination of shear instability around the mainstream of the Kuroshio with prominent baroclinic instability near the Kuroshio front is essential for the generation of eddies in the KR, leading to the increase of the eddy‐induced vertical nitrate transport around the Kuroshio. Key Points: The primary production along the Kuroshio is examined using a climatological, high‐resolution, coupled circulation‐biogeochemical model Eddy‐driven downward nitrate transport suppresses the primary production in the Kuroshio Region by shear and baroclinic instabilities In turn, the downwelling is much less pronounced in the Kuroshio Extension, where nitrate upwelling due to cyclonic eddies prevails